Workplace violence among nurses working in public hospitals in Northern Ethiopia; a mixed method study - Abirha, Mamush Gidey; Gebreslassie, Kibrom Berhanu; Abera, Gerezgiher Buruh; Tesfay, Binyam Gebrehiwet; Mesele, Fissha Brhane; Gebreanenia, Fiseha Abadi; Weldu, Kelali Goitom; Bahre, Willi; Woldemariam, Guesh Teklu (Frontiers in Public Health, 2025)
BackgroundWorkplace violence has become a warning universal phenomenon, particularly affecting healthcare workers, especially nurses. This study aimed to assess the prevalence of workplace violence and its associated factors among nurses working in public hospitals in Northern Ethiopia.MethodsA mixed-methods study was conducted at a hospital in Northern Ethiopia among 416 nurses using a self-administered questionnaire. A simple random sampling technique was employed to select the participants. Descriptive, bivariate, and multivariable logistic regression analyses were performed using the Statistical Package for Social Sciences (SPSS) version 27. For the qualitative part, critical case purposive sampling was used to select respondents, and data were collected through face-to-face, in-depth interviews. Finally, inductive thematic analysis was performed on the data using ATLAS.ti 23.ResultThe prevalence of workplace violence among nurses in the last 12 months was 62.8% (95% CI, 57.5–76.3). Working in the emergency department was associated with a significantly increased risk (AOR = 4.97, 95% CI: 1.10–22.70, p = 0.039). Conversely, being married (AOR = 0.58, 95% CI: 0.34–0.98, p = 0.046) and having a good work performance (AOR = 0.59, 95% CI: 0.36–0.96, p = 0.03) were associated with a significantly decreased risk. Additionally, having 1–5 staff members in the same working area (AOR = 3.40, 95% CI: 1.12–10.40, p = 0.030) and working alone (AOR = 2.34, 95% CI: 1.34–4.10, p = 0.003) were significant factors. Nurses perceived understaffing, shortage of drugs and supplies, lack of security, and lack of management attention to workplace violence as the main reasons behind these incidents.ConclusionWorkplace violence among nurses was found to be significantly high in the study area. We recommend that it is essential for the health sector to establish a strong system for preventing and reporting incidents of workplace violence by involving medical personnel.